AIR SUSU IBU MENCEGAH IKTERUS PADA NEONATUS DINI : EVIDENCE BASED CASE REPORT (EBCR) (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: Jaundice is a yellow discoloration of the skin or other organs due to accumulation of bilirubin. Neonatal jaundice is a problem that often occurs in newborns, namely a condition where the bilirubin level is >10 mg%. To control bilirubin levels in newborns, drinking can be done as early as possible with adequate amounts of fluids and calories. Purpose: The purpose of this report is to find out whether early or early breastfeeding can prevent jaundice in newborns aged 7 days. Method: The article search method uses the PubMed and Garuda databases. Intervention is carried out by asking the mother to start breastfeeding her baby after 1 hour post partum or after IMD is carried out. Result: The results of the report used the MTBM examination which was carried out when the baby was 7 days old and the result was that the baby did not experience jaundice or other diseases. Conclusion: Early breastfeeding is effective in preventing jaundice in newborns.